2017
DOI: 10.1177/1094670517711586
|View full text |Cite
|
Sign up to set email alerts
|

Customer Interaction and Innovation in Hybrid Offerings

Abstract: Hybrid offerings are bundles of goods and services offerings provided by the same firm. Bundling value offerings affects how firms innovate, interact with customers, and customize their goods and services. However, it remains unclear how customer interaction might drive the innovation performance of various bundled components. Therefore, this study investigates the effects of customer interactions and service customization on both goods and services innovations in a hybrid offering context, using a unique data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(33 citation statements)
references
References 93 publications
(132 reference statements)
1
32
0
Order By: Relevance
“…Following this logic, employee innovation behavior not only relies on an individuals' information and skills, but also on outside resources and capital. This means employees need to seek help from outside of company structures-for example from customers to access resources and information useful to innovation (Foss et al, 2011;Schaarschmidt et al, 2018). Customer behaviors have been seen as important antecedents to employee innovative behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Following this logic, employee innovation behavior not only relies on an individuals' information and skills, but also on outside resources and capital. This means employees need to seek help from outside of company structures-for example from customers to access resources and information useful to innovation (Foss et al, 2011;Schaarschmidt et al, 2018). Customer behaviors have been seen as important antecedents to employee innovative behavior.…”
Section: Introductionmentioning
confidence: 99%
“…In furtherance to that innovation, quality has an impact on new service market performance. In a related work by Schaarschmidt & Walsh, (2018) which focused on customer interaction in the B2B business, using a unique data set of 146 information technology and manufacturing firms, an interview was conducted which revealed that customer interaction appears beneficial to both goods and services innovation in a hybrid offerings context. The ongoing discussions lead the study to hypothesize that:…”
Section: Market Knowledgementioning
confidence: 99%
“…Customer interaction has been understood as the different forms of information exchange, collaboration and cooperation that occur between a company and its customers, it is a continuous value generator for organizations (Gruner and Homburg, 2000). Customer interaction is directly associated with the mechanisms firms use to innovate, interact with customers and customize their goods and services (Schaarschmidt et al , 2018). It has therefore been suggested that this concept has become a new marketing paradigm (Storbacka et al , 1994).…”
Section: Understanding and Reflecting On The Customer Interaction Constructmentioning
confidence: 99%
“…However, the impacts of customer interaction at the firm level can be different forms of information exchange, collaboration and cooperation, rather than a simple relationship between consumers and businesses. For customer interaction generate strong results, the company must create mechanisms that continuously support the interaction and make the customization of their goods and services possible (Schaarschmidt et al , 2018).…”
Section: Academic and Practical Implicationsmentioning
confidence: 99%
See 1 more Smart Citation